PERILAKU OKSIDASI ISOTERMAL PADUAN 68,5Fe-14Ni-9Al-7,5Cr-1Mo PADA TEMPERATUR 800, 900, DAN 1000°C - Muhammad, Fadhli; Basuki, Eddy Agus (Jurnal Rekayasa Mesin, 2024)
Extensive research has been conducted on high-temperature alloys for power generation, with chromium-forming ferritic iron as the primary basis for these materials. However, the practical applications of these materials are limited to temperatures below 800°C. This study addresses the development of an alumina-forming 68.5Fe-14Ni-9Al-7.5Cr-1Mo austenitic iron-based alloy, isothermally oxidized at 800, 900, and 1000°C for 1, 10, 50, and 150 h, respectively. The formation of the protective layer was characterized using X-ray diffraction (XRD) and energy dispersive spectroscopy (EDS) attached in a scanning electron microscope (SEM). The thickness of the oxide layer was quantified using the ImageJ software. XRD analysis of the sample that had been oxidized for 150 h at various temperatures revealed the presence of Al2O3. The clustered grain morphology was observed at the sample's surface oxidized for 150 h at 800°C. In contrast, the sample oxidized at 900°C exhibited a hair morphology, and the sample oxidized at 1000°C exhibited a wrinkled morphology. EDS mapping of all samples revealed that O and Al dominated the oxide scales. Measurements of oxide thickness indicated an accelerated growth phase during the first 10 hours of exposure, which was subsequently followed by a gradual slowing down in growth rates over more extended periods of time